Automated Chemical Shift Assignments of MAS Solid-State NMR Spectra of Complex Protein Systems by ssPINE/ssPINE-POKY - Andrea Estefania Lopez Giraldo; Mehdi Rahimi; Woonghee Lee (Applied Sciences)
Solid-state nuclear magnetic resonance (ssNMR) spectroscopy enables studying complex macromolecules with low solubility. Compared to solution NMR, few tools exist for biomacromolecule ssNMR data analysis. A key challenge is assigning spin systems due to low peak dispersion. Broad peaks from large dipolar couplings and shift anisotropy cause significant overlap and missing peaks. To address this, we introduce ssPINE-POKY, a user-friendly graphical user interface (GUI) integrated into the POKY suite. ssPINE-POKY streamlines the automation of spin system recognition and chemical shift assignment in multidimensional ssNMR spectra by integrating the ssPINE algorithm within an intuitive interface. The platform allows easy and fast job submission, real-time result visualization, and enhanced analysis through additional built-in tools, significantly improving the efficiency of ssNMR data interpretation.